INITIAL RETURN DAN RETURN 7 HARI SAHAM-SAHAM IPO DI BURSA EFEK INDONESIA - Rahmanto, Basuki Toto; Suriawinata, Iman Sofian (Economic Faculty, Attahiriyah Islamic University, 2019)
The purpose of the study is to determine whether financial information that is proxied by the current ratio, return on assets, and debt to equity ratio and non-financial information proxied by auditor reputation, percentage of stock offerings, company age, and government ownership affect initial return and stock return 7 days. The sample used in this study are companies that conduct initial public offerings on the Indonesia Stock Exchange for the period of 2012 to 2016. The sampling method used was purposive sampling and the statistical method used is linear regression. The results of the study obtained the debt equity ratio, auditor reputation and company age negatively affected the initial return. The return of 7 days after the IPO is not influenced by financial and non-financial information, but the initial return affects the return of 7 days after the IPO in a positive direction. Keywords: initial return, return 7 day post IPO